Qaraqalpaq tilindegi tekstti sóylewge sintezlew sisteması ushın maǵlıwmatlar bazasın qáliplestiriw - Mamatov, N.S; Jalelov, K.M; Samijonov, B.N; Samijonov, A.N; Madaminjonov, A.D (SCIENCE and SOCIETY, 2023)
Speech synthesis is the conversion of an arbitrary text given in a natural language into spoken form in that language. A high-quality speech database is essential for creating speech synthesis systems. Currently, such databases have been created for many languages, but no speech database has been created to translate text information in the Karakalpak language. Therefore, it is urgent to create a speech database for converting Karakalpak text into speech. This article is devoted to the problems and their solutions related to the creation of a speech database in the Karakalpak language.
Keywords: text; speech; speech database; digital signal processing (DSP)